The Influence of the Tax Penalty Bleaching Program, Exemption of Transfer of Title Fees and Exemption of Motor Vehicle Tax Arrears for the 5th Year on Motor Vehicle Taxpayer Compliance - Haqeza Kaldha; Yuppy Triwidatin (PT FORMOSA CENDEKIA GLOBAL, 2023)
West Java Province is currently holding a program of eliminating fines and discounting vehicle taxes, which were carried out in the context of economic recovery by the government after the Covid-19 pandemic. This study aims to determine how much influence the bleaching program planned by the government has on motor vehicle tax compliance. This is an attempt by the local government to attract motor vehicle tax revenue by providing local tax relief and exemption (bleaching). The research design used is quantitative research with survey methods, the population is motorized vehicle taxpayers in the PPPD Sukabumi 1 Cibadak Regency, namely as many as 369,165 people with samples taken are 100 motorized vehicle taxpayers with the sampling used is a simple technique random sampling. The results of the study show that the program for the cancellation of tax fines, the exemption of transfer fees, and the 5th year motor vehicle tax arrears exemption simultaneously have a significant effect. Partially, it shows that the program for the elimination of tax fines, exemption from transfer fees, and the 5th year motor vehicle tax arrears exemption has a significant effect on motor vehicle taxpayer compliance.